2018
DOI: 10.1016/j.contraception.2018.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the capacity of California's publicly funded universities to provide medication abortion

Abstract: If SB320 is passed, provision of MA services at student health centers could improve access to early abortion for students in California. This model may be scaled up at other universities around the country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The majority of college or university student health centers (SHCs) nationwide provide some sexual and reproductive health services, which may include abortion counseling or referral, and Healthy Campus 2020 includes multiple objectives to improve student sexual and reproductive health [4,10]. As disparities to access increase nationally, research indicates SHCs can reduce critical determinants of reproductive and abortion care access such as travel distance, facilitate retention and graduation, and impact rural and other college students who face a limited and decreasing number of providers [3,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of college or university student health centers (SHCs) nationwide provide some sexual and reproductive health services, which may include abortion counseling or referral, and Healthy Campus 2020 includes multiple objectives to improve student sexual and reproductive health [4,10]. As disparities to access increase nationally, research indicates SHCs can reduce critical determinants of reproductive and abortion care access such as travel distance, facilitate retention and graduation, and impact rural and other college students who face a limited and decreasing number of providers [3,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It is unique in assessing whether and which types of reproductive health barriers exist and how they differ in the community healthcare system versus on campus. While data on projected student medication abortion rates, reproductive health barriers, and SHC staff perspectives exist, we sought to document student voices, experiences, and needs [1,3,7,14].…”
Section: Introductionmentioning
confidence: 99%
“…35 Previous research in California before medication abortion was required on campuses showed that all SHCs either met the evidence-based requirements to provide medication abortion or could meet these requirements with modest investment. 36 Research also suggests telehealth medication abortion services can feasibly be implemented in diverse clinical settings, including those similar to SHCs. 37 This study is limited by the estimated proportion of medication abortions which is for all women of reproductive age and not specific to this age group.…”
Section: Discussionmentioning
confidence: 99%
“…39 Previous research in California before medication abortion was required on campuses showed that all student health centers either met the evidence-based requirements to provide medication abortion or could meet these requirements with modest investment. 40 Additionally, to provide students with both telehealth and in-person visit options, research suggests that telehealth medication abortion services can feasibly be implemented in diverse clinical settings, including those similar to student health centers. 41 While ultrasounds are commonly cited as a costly implementation barrier, the current scientific consensus is that ultrasounds are not needed for effective and safe first-trimester medication abortions.…”
Section: Discussionmentioning
confidence: 99%